Branch duct intraductal papillary mucinous neoplasms of the pancreas: watch and wait is not harmless : letters to the editor - Fritz, Stefan; Werner, Jens; Büchler, Markus W. (Pancreas, 2013)
An abstract is unavailable.
Gesehen am 07.06.2021